GAMBARAN PERILAKU CUCI TANGAN PAKAI SABUN (CTPS) PADA SISWA SEKOLAH DASAR KELAS V - Silawati Ningsih, Tengku Hartian (MIDWIFERY JOURNAL, 2021)
Background: Hand washing is the activity of cleaning the palm, back of your hands and fingers to be cleaner than dirt and kill germs causing diseases that harm human health and make the hands smell good. Hand washing can reduce the number of bacterial colonies attached to the hands, and prevent the transmission of bacteria and diseases from one person to another. According to pauzan and hudzaifah al-fatih research, students' knowledge of hand washing is almost half (41.0%) students have a good level of knowledge, a small fraction (21.8%) students have a sufficient level of knowledge, and nearly half (37.8%) students have less knowledge, the results may be related to counseling about hand washing given by one of the soap products one week before the study begins.Purpose:Therefore, this research was conducted aimed at identifying the implementation factor of hand washing in grade v students in 194 Pekanbaru public elementary school in 2019.Methods: This type of research uses qualitative research types with descriptive research designs. The number of samples in this study was 91 respondents, taken using total sampling techniques. By collecting data using questionnaires and then done manual data processing (editing, coding sheet, tabulation), presented univariate data analysis.Results: The results of the study conducted on 91 respondents showed that the majority of respondents' knowledge was sufficient as much as 53 people (58.24%), the majority of positive respondents were 50 people (54.94%) and the respondent's school facilities were good as much as 69 people (75.82%).Conclusion: It can be concluded that the majority of respondents have implemented clean and healthy living but are still influenced by several factors in applying this including knowledge, attitudes and facilities in the school. To improve the knowledge and positive attitude of respondents towards cleanliness, it is necessary for the school to provide health education about clean living periodically.Suggestion It is hoped that the school can continue to monitor students in the application of continuous hand washing with soap.  Keywords: Application, Hand Washing and CTPS ABSTRAK Pendahuluan: Mencuci tangan adalah kegiatan membersihkan bagian telapak, punggung tangan dan jari agar lebih bersih dari kotoran dan membunuh kuman penyebab penyakit yang merugikan kesehatan manusia serta membuat tangan menjadi harum baunya. Mencuci tangan dapat mengurangi jumlah koloni bakteri yang menempel pada tangan, dan mencegah penularan bakteri dan penyakit dari satu orang ke orang yang lain. Menurut hasil penelitian Pauzan dan Hudzaifah Al-Fatih Tingkat pengetahuan siswa tentang cuci tangan hampir separuh (41.0%) siswa memiliki tingkat pengetahuan yang baik, sebagian kecil (21.8%) siswa memiliki tingkat pengetahuan yang cukup, dan hampir separuh (37.8%) siswa memiliki tingkat pengetahuan kurang, hasil tersebut mungkin terkait dengan diadakannya penyuluhan tentang cuci tangan yang diberikan oleh salah satu produk sabun satu minggu sebelum penelitian dimulai.Tujuan Penelitian: penelitian ini bertujuan untuk mengidentifikasi gambaran faktor penerapan cuci tangan pada siswa kelas v di sekolah dasar negeri 194 Pekanbaru tahun 2019.Metode: Jenis penelitian ini menggunakan jenis penelitian Kuadengan desain penelitian deskriptif. Jumlah sampel pada penelitian ini berjumlah 91 responden, diambil dengan menggunakan teknik total sampling. Dengan pengumpulan data menggunakan kuesioner dan kemudian dilakukan pengolahan data secara manual (editing, coding sheet, tabulasi), disajikan analisis data univariat.Hasil penelitian: yang dilakukan pada 91 responden menunjukkan bahwa mayoritas pengetahuan responden cukup yaitu sebanyak 53 orang (58,24%), mayoritas sikap responden positif yaitu sebanyak 50 orang (54,94%) dan fasilitas sekolah responden adalah baik yaitu sebanyak 69 orang (75,82%).Kesimpulan: Dapat disimpulkan bahwa mayoritas responden telah menerapkan hidup bersih dan sehat karena didukung oleh beberapa faktor diantaranya pengetahuan, sikap dan fasilitas yang ada di sekolah.Saran Diharapkan pihak sekolah untuk dapat terus memantau siswi dalam penerapakn cuci tangan dengan sabun secara continue.  Kata Kunci: Penerapan, Cuci Tangan dan CTPS.